Assessment of the Usefulness of Observation and Tracking Heads of the Long-Range for the Stratospheric Aerostat Recognition System - Paweł DOBRZYŃSKI; Mariusz KRAWCZAK; Stanisław LIPSKI; Bogdan MACHOWSKI (Problemy Mechatroniki, 2018)
The paper presents the problems of applications of stratospheric systems to increase the tactical and reconnaissance capabilities of the Polish Armed Forces. The paper contains the results from examples of simulations which were designed to determine the cost/performance ratio of the production and operation of aerostats with strictly identified technical parameters in the context of their operational capabilities. It also describes the principles of operation of aerostats for the support of intelligence collection and the limitations imposed on aerostats by the specificity of tropospheric and stratospheric regions.